The Effect Of Giving A Combination Of Mirror Therapy And Rom (Range Of Motion) Based On Self Care Theory On Muscle Strength In Stroke Patients - Nadatien , Ima; Salamah, Umi; Hidaayah, Nur (Chakra Brahmanda Lentera Institute, 2024)
Background: Stroke is a state of neurological deficit that occurs when some brain cells die due to flow disturbances. Stroke patients experience hemiparesis and have limitations in upper and lower limb motor function and motor function, leading to limitations on functional mobility. According to Riskesdas (2020) Indonesia, the prevalence of stroke has increased from 7% to 10.9%, while stroke sufferers in East Java are 507 people. The purpose of this study was to analyze the effect of giving a combination of mirror therapy and ROM based on self care theory on muscle strength in stroke patients in the Inpatient Room of RSI Darus Syifa' Surabaya Methods: This type of research used True Experimental with Pretest-Posttest Control Group Design. The population in this study were 103 stroke patients. The sampling technique used probability sampling by simple random sampling, the sample size in this study was 34 respondents, 17 respondents for the control group and 17 respondents for the intervention group. The instrument for measuring muscle strength used the Medical Research Council (MRC) scale. The data obtained were analyzed using Wilcoxon Sign Rank Test and Mann Whitney. Results: The results of Mann Whitney on muscle strength variables with a significant level of 0.000 < = 0.05, indicate that there is an effect of a combination of mirror therapy and rom (range of motion) based on self care theory on strength. muscles in stroke patients in the inpatient ward of the rsi darus syifa 'surabaya. Conclusion: The conclusion of this study is that the combination of mirror therapy and ROM based on self care theory has an effect on muscle strength in stroke patients and is easy to do, so that it can be applied as a nursing intervention in inpatient rooms for the development of nursing science in hospitals.